Lupeol in Functional Gastrointestinal Disorders: An Evidence-based Preclinical Study - Das, Saumya; Shafiq, Nashra; Das, Manas Kumar; Kumar, Vikas; Rajangam, Jayaraman (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: The current study assessed the possible use of lupeol in the treatment of intestinal inflammation for the initial instance and for the anxiolytic activity for the management of Functional Gastrointestinal Disorder (FGID) by two different models of colitis (IBD) TNBS and DSS and by two anxiolytic models EPM and OFT. Materials and Methods: The intestinal anti-inflammatory models of colitis were performed by using TNBS and DSS to obtain the possible use of lupeol at a dose of 25μg/mL and 50μg/mL in Irritable Bowel Disease (Ulcerative Colitis). In both experiments, Albino Wistar rats were divided into 5 groups and each group contain six animals. During the experiment change in body weight, stool consistency and colon weight/length as well as a histological examination of the colon were performed. For the anxiolytic activity EPM and OFT models were used. In both, the model’s Swiss albino mice were used and they were divided into four groups and each group containing six animals. In EPM model, each mouse was positioned in the centre of the maze, facing an enclosed arm. For 5 min, the number of entries and duration spent in open arms was monitored. Increased open-arms entry and time spent in open arms were viewed as indicators of possible anxiolytic activity. In OFT model animals were brought separately to the centre of the arena just after intervention and then exposed to a 5-min open field test. Throughout the experiment, the mice's overall social behaviours were recorded, including the total number of crossings, time spent in the arena, as well as central arena. In both models of anxiolytic, all the interventions were given intraperitoneal (i.p.) 30 min before the experiment began. Results: In this research work both the screening procedures of colitis were linked to up-regulation of pro-inflammatory enzymes in inflamed mucosal tissues in the current investigation, indicating that it has considerable anti-inflammatory impacts in the intestine. The findings of this study enhance the rationale for additional research into the medicinal benefits of lupeol in the management of human IBD. Anxiety, sleeplessness, and psychosis are all common in today's fast-paced world, which is filled with a variety of high-stress situations. According to the findings, the bioactive phytoconstituent triterpenoid lupeol had a substantial antianxiety impact in mice. The current study found that colonic inflammation was linked to increased free radicals in the CNS and ENS, as predicted by the results of the IBD and anti-anxiety screening models. Furthermore, the findings demonstrated that lupeol was able to alleviate experimental colitis and anxiety symptoms, both of which are important FGID phenomena.
Keywords: Functional Gastrointestinal Disorder; Irritable Bowel Disease; Trinitrobenzene sulfonic acid; Dextran Sodium Sulfate; Lupeol